The Development Strategy of Sustainable Competitive Advantageat Indonesian PHEIs - Muhammad Yusuf S Barusman (Bandar Lampung University (UBL), 2013)
The competition amonghigher education institutionsin Indonesia has been becoming tougher since a decade ago, especially in new student enrollment period. This phenomenon is very interested to be studied because PHEIs (PHEI),which had operated less or more than ten years, could hold out in the situation. The objectives of this research are to analyze the determining factors that influence the sustainability of the PHEIs (PHEI), to analyze future scenarios regarding dynamic of external environmentof PHEIs (PHEI), and to develop the best strategy to face the most possible scenario occurred. Data collection was done by textual analysis, in-depthinterview, focus group discussion and questionnaire. Data was analyzed descriptively through Analytical Hierarchy Process (AHP), Participatory Prospective Analysis (PPA) and Exponential Comparison Method (ECM). The study finds that there are four internal and five external determining factors that influencesustainability of PHEIs. In addition, there are 72 scenarios concerning the dynamic of external environment that could be happened in the future. To overcome the most possiblescenario that could be happened in the future, PHEIs could develop strategy by combining the main internal factor, namely leadership effectiveness, financing availability, effectiveness of human resource management and curriculum relevance